Examining the interplay of employee brand love, affective commitment, positive word of mouth, and turnover intention - Shrestha, Rijma; Pokhrel, Laxman (Journal of Emerging Management Studies, 2023)
Purpose - The purpose of this paper was to examine the interplay of Employee Brand Love (EBL), Affective Commitment (AC), Positive Word of Mouth (PWM), and Turnover Intention (TI) among employees of different organizations in the service sector. Design/methodology/approach - This research study employed a cross-sectional survey research design and utilized a purposive sampling technique to collect data from a sample of 251 respondents. To assess the hypotheses, we utilized the Process Macro 3.5 Free Version software. Finding - The findings indicate that EBL exerts a significant impact on PWM and TI, but its influence on AC is found to be insignificant. Furthermore, the results demonstrate that AC serves as a partial mediator in the relationship between EBL and both PWM and TI. Practical Implications - This study could help managers to better understand especially how brand love of employees affects employee intention to leave the organization. It might help to increase the likelihood that employees will love their organizational brands and, as a result, design branding strategies to strengthen the organizational brand in order to draw in new employees and promote organizations.